The Role of Spokesperson during the Covid-19 Pandemic in East Nusa Tenggara Province - Kotten, Fian S.; Hana, Ferly Tanggu; Mandaru, Silvania S.E. (Asian Journal of Media and Communication, 2023)
The crisis caused by the Covid-19 made local governments take over public communication in order to deliver accurate information about the pandemic to the public. Taking the case of East Nusa Tenggara (NTT) provincial government, this article focuses on the role of spokesperson to deliver the Covid-19 pandemic information. In this province, the spokesperson was the Head of public relations and protocol bureau of the provincial secretariat of the NTT Province. As a public communicator of the NTT Provincial Government during the pandemic, he has played an important role in communicating information from the government to the public, including information provider and gatherer, government’s media manager for extending pandemic information to the society, and government’s representative.